Pelatihan Ecoprint untuk Meningkatkan Kreativitas dan Ide Bisnis Ibu PKK Desa Kedungpeluk, Kecamatan Candi, Sidoarjo - Verina Rais Annisa; Arealdo Robiq Yustiawan; Umi Alfia; Dewi Puspa Arum (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Ecoprint is a form of creative art that uses natural materials such as leaves, flowers and tree bark using a paint printing process on natural fibrous resources. This community service activity was carried out to provide training for PKK women in Kedungpeluk village, to be able to produce quality ecoprint products that have high selling value, to provide opportunities for women to develop their potential, increase independence, and play an active role in village development, and the ecoprintproducts produced It is hoped that it can become a characteristic of Kedungpeluk Village and increase local tourist attraction. This service activity was carried out at the Kedungpeluk Village Hall, Candi District, Sidoarjo Regency using direct lecture and practical methods. The activity was attended by 33 PKK women from Kedungpeluk Village. All participants were able to do the ecoprint pounding technique well on a tote bag which was then taken home by each participant.